Power and Resistance in A Singapore Film: La Luna - Abigail Welby Junuslie; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This article discusses a Singapore film, La Luna. This film tells the story of Hanie, a modern business woman from a big city who opens a lingerie shop in a conservative village of Bras Basah. The villagers gradually welcome the shop with open arms. However, the religious leader of the village, Tok Hasan, sees that the store threatens as the religious values of the society, and thus he wants to drive the shop out of the village. Through the story of Hanie, La Luna exposes several important issues such as corrupted power, authoritarian leader, oppression, and resistance. Because of these issues, we are interested in analyzing this film. By using Michel Foucault’s theory of power and resistance and James Scott’s theory of everyday resistance, we investigate the way Tok Hassan exercises his religious power and the way the villagers resist his power. We find out that Tok Hassan exercises his religious power by establishing laws and rules, surveilling the act of villagers and also using violence. In response, the villagers show their resistance by protesting, disobeying and making an ally. Even though it has to be carried out slowly, the action was successful to bring change in the village. All these show that even under oppressive conditions, resistance will always exist in its own way.